Synthesis of influenza virus polypeptides in cells resistant to alpha-amanitin: evidence for the involvement of cellular RNA polymerase II in virus replication. - Lamb, R A (1977)
Influenza virus polypeptides were not synthesized in wild-type CHO-S-infected cells in the presence of alpha-amanitin, but were synthesized in CHO-Amal cells, a mutant cell line whose DNA-dependent RNA polymerase II is specifically resistant to this drug, indicating that this cellular enzyme is involved in influenza virus replication. The results of experiments designed to detect viral polypeptides synthesized from primary transcripts suggest that the synthesis of a cellular RNA species by RNA polymerase II is required for primary transcription of the influenza virus genome.